New Political Campaigning in the Digital Era: Khofifah Indar Parawansa's Strategy during the 2024 East Java Regional Elections - Hanggaratri, Candra Ayu; Rahmawati, Dian Eka; Misran, Misran; Asruddin, Fajar Aswad (Politicon : Jurnal Ilmu Politik, 2025)
This research examines new political marketing strategies in the digital era through Instagram, focusing on Khofifah Indar Parawansa's political campaign in the 2024 East Java Regional Head Election. This research uses a qualitative method with a virtual ethnographic approach, this study analyzes the content of Khofifah's official Instagram account. The results of the study show that Khofifah successfully uses social media to convey personal narratives that are packed with local and religious cultural values, build emotional bonds with the community, and create effective two-way interactions through attractive visual uploads such as photos, videos, and stories. The study also underscores the importance of balancing social media to expand campaign reach efficiently and cost-effectively, while addressing challenges such as polarization, disinformation, and the digital divide. This research contributes to the political marketing literature by highlighting Instagram's role in building candidate brands at the local level, especially among young voters. These findings provide practical guidance for political practitioners in optimizing social media to create more effective and inclusive campaigns.